Systematization of a training process of community promoters: thoughts and learned lessons on participation and volunteer - Tarazona Cervantes, David (2011)
This article discusses the training of promoters in a program to promote community libraries. Systematization is a critical rearrangement of the events into an experience to understand the reasons that it develops in a specific way and not otherwise. Two processes are reconstructed first, the overall project cycle during which develops the experience and then, secondly, we present the development of process specific training of community. It ends by presenting the lessons learned identified and developed.